2010
DOI: 10.1364/oe.18.018003
|View full text |Cite
|
Sign up to set email alerts
|

Theory of passively mode-locked photonic crystal semiconductor lasers

Abstract: Abstract:We report the first theoretical investigation of passive mode-locking in photonic crystal mode-locked lasers. Related work has investigated coupled-resonator-optical-waveguide structures in the regime of active mode-locking [Opt. Express 13, 4539-4553 (2005)]. An extensive numerical investigation of the influence of key parameters of the active sections and the photonic crystal cavity on the laser performance is presented. The results show the possibility of generating stable and high quality pulses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The insets show the temporal variation of the laser output power at the indicated points in the phase space. The laser output is categorised using a combination of the signal variance and the number and nature of the peaks observed (increasing, decreasing, constant) in order to correctly identify the type of laser operation, similar to the method used in [28]. Finally, the dashed black line indicates the borders of self-pulsing predicted by a stability analysis of the dynamical equations, showing very good agreement with the dynamical simulations.…”
Section: Modes Of Laser Operationmentioning
confidence: 82%
See 2 more Smart Citations
“…The insets show the temporal variation of the laser output power at the indicated points in the phase space. The laser output is categorised using a combination of the signal variance and the number and nature of the peaks observed (increasing, decreasing, constant) in order to correctly identify the type of laser operation, similar to the method used in [28]. Finally, the dashed black line indicates the borders of self-pulsing predicted by a stability analysis of the dynamical equations, showing very good agreement with the dynamical simulations.…”
Section: Modes Of Laser Operationmentioning
confidence: 82%
“…Future work should clarify the role of spontaneous emission noise on the laser performance, including intensity noise and timing jitter of the pulses. It is also of interest to explore structures for realizing mode‐locked operation . In general, several of the laser geometries that are found to be of interest for realizing specific dynamical laser properties could be reconsidered using the option of incorporating a Fano resonance.…”
Section: Conclusion and Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Approaching the band edge, the group refractive index increases and slow-light propagation effects prevail, with a number of possible applications, e.g., for tunable delays [1,2], enhanced light-matter interaction, optical switching [3], nonlinear optics [4,5], and mode-locked lasers [6]. It has been reported that both material loss and material gain in the PhCWs restrict the attainable group index and degrade slowlight effects [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This framework could be used to investigate the impact of dispersion on the dynamics of a broad (8)- (9), (7) for ΔðtÞ ¼ Δ 0 sin ρt at the turning point of the filter transmission sin ρt ¼ −1 (top) in case of (a) normal dispersion Ω ¼ 13 (modulation frequency ρ ¼ 10 class of systems commonly described by DDEs. For example, this approach could be used to understand the effect of linear chromatic dispersion on the characteristics of the mode-locked regime in monolithic multisection lasers and other nonlinear photonic devices [6,7,10,[21][22][23][24][25][26]. In particular, taking chromatic dispersion into consideration is unavoidable when modeling soliton mode-locked lasers frequently used for generation of femtosecond pulses [27], photonic crystal mode-locked lasers [25], as well as many other fiber, solid state, and semiconductor [28] optical systems.…”
mentioning
confidence: 99%